Isolation, Culture, and Staining of Single Myofibers - Yann Gallot; Sajedah Hindi; Aman Mann; Ashok Kumar (Bio-Protocol, 2016)
Adult skeletal muscle regeneration is orchestrated by a specialized population of adult stem cells called satellite cells, which are localized between the basal lamina and the plasma membrane of myofibers. The process of satellite cell-activation, proliferation, and subsequent differentiation that occurs during muscle regeneration can be recapitulated ex vivo by isolation of single myofibers from skeletal muscles and culturing them under suspension conditions. Here, we describe an improved protocol to evaluate ex vivo satellite cells activation through isolation of single myofibers from extensor digitorum longus (EDL) muscle of mice and culturing and staining of myofiber-associated satellite cells with the markers of self-renewal, proliferation, and differentiation.